The fractal dimension of an oil spray - Castrejón García, R; Sarmiento Galán, A; Pita, C; Castrejón Pita, A (2003)
We study the fractal dimension of the contour of the liquid-gas interface in a spray. Our images include both the linking region and the break-up region, and are obtained with a highresolution shadowgraph technique. This means that the images can then be subjected to an intensity filtering, equivalent to a threshold analysis, that enables the establishment of the fractal range.